Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/ncb3254
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput platform for real-time analysis of membrane fission reactions reveals dynamin function

Abstract: Dynamin, the paradigmatic membrane fission catalyst, assembles as helical scaffolds that hydrolyse GTP to sever the tubular necks of clathrin-coated pits. Using a facile assay system of supported membrane tubes (SMrT) engineered to mimic the dimensions of necks of clathrin-coated pits, we monitor the dynamics of a dynamin-catalysed tube-severing reaction in real time using fluorescence microscopy. We find that GTP hydrolysis by an intact helical scaffold causes progressive constriction of the underlying membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 38 publications
15
76
2
Order By: Relevance
“…7e). Our data further show that dynamin 2 in spite of its tubulation activity on artificial lipid templates in vitro 132131 is insufficient for efficient constriction of U-shaped endocytic intermediates in mammalian cells in vivo, consistent with recent results from model membrane templates32. PX-BAR protein-mediated constriction of invaginated CCPs is also consistent with recent correlative light and electron microscopic data showing that endocytic intermediates mature by continuous membrane remodelling17 known to be driven by BAR domain proteins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7e). Our data further show that dynamin 2 in spite of its tubulation activity on artificial lipid templates in vitro 132131 is insufficient for efficient constriction of U-shaped endocytic intermediates in mammalian cells in vivo, consistent with recent results from model membrane templates32. PX-BAR protein-mediated constriction of invaginated CCPs is also consistent with recent correlative light and electron microscopic data showing that endocytic intermediates mature by continuous membrane remodelling17 known to be driven by BAR domain proteins.…”
Section: Discussionsupporting
confidence: 91%
“…How this lipid-based mechanism couples membrane constriction to membrane fission is unknown. In vitro studies have found that helical assemblies of multiple dynamin rings can mediate constriction and fission of large liposomal membrane templates13213031, while recent work using physiological PI levels shows that dynamic scaffold assembly depends on the presence of a constricted membrane template32, suggesting that additional factors may be required to provide such a template for dynamin-mediated constriction and fission in vivo . Moreover, model membranes lack stabilizing proteins and are, thus, more flexible than the plasma membrane in living cells, where dynamin associates with highly curved membranes of about 20 nm diameter corresponding to its preferred membrane template in vitro 3334.…”
mentioning
confidence: 99%
“…, 2012), exhibits fluorescence properties that are insensitive to protein binding (Jung et al. , 2009), and displays unrestricted diffusion in membrane tubes (Dar et al. , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, this observation is consistent with the fact that the super‐constricted state of dynamin does not constrict the membrane sufficiently to reach hemi‐fission, leaving a lumen of 1.9 nm radius (see Fig ) (Sundborger et al , ): In a case where dynamin would constrict the membrane enough to go beyond the hemi‐fission state and break it completely, membrane tension would have no impact on the fission rate, as a membrane with low tension would be broken as efficiently as a membrane with high tension. However, fission occurs within minutes if membrane tension is low (Pucadyil & Schmid, ; Dar et al , ), whereas it takes a few seconds when membrane tension is high (Roux et al , ; Bashkirov et al , ; Morlot et al , ), showing indeed that tension has a direct impact on fission efficiency. Moreover, upon dynamin‐mediated constriction, the hemi‐fission state is reached stochastically (Shnyrova et al , ; Mattila et al , ) and is reversible, suggesting that once constricted, thermal fluctuations of the membrane are needed to reach the hemi‐fission state.…”
Section: What Is Being Discussed: Reconciling Gtp‐driven Constrictionmentioning
confidence: 99%